2017
DOI: 10.1038/s41598-017-07649-z
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumour Cell Release after Cement Augmentation of Vertebral Metastases

Abstract: Cement augmentation via percutaneous vertebroplasty or kyphoplasty for treatment of spinal metastasis is a well-established treatment option. We assessed whether elevated intrametastatic pressure during cement augmentation results in an increased dissemination of tumour cells into the vascular circulation. We prospectively collected blood from patients with osteolytic spinal column metastases and analysed the prevalence of circulating tumour cells (CTCs) at three time-points: preoperatively, 20 minutes after c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 49 publications
0
19
0
3
Order By: Relevance
“…The intervention we report, and especially the injection of cement into the tumor mass without prior tumor ablation, may have induced dissemination of tumor cells into the blood stream. Mohme et al reported a temporary increase in the number of circulating tumor cells in the peripheral blood 20 min after vertebroplasty or balloon kyphoplasty [16]. However, whether this increase affects the survival of patients with bone metastases is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intervention we report, and especially the injection of cement into the tumor mass without prior tumor ablation, may have induced dissemination of tumor cells into the blood stream. Mohme et al reported a temporary increase in the number of circulating tumor cells in the peripheral blood 20 min after vertebroplasty or balloon kyphoplasty [16]. However, whether this increase affects the survival of patients with bone metastases is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether this increase affects the survival of patients with bone metastases is unknown. Also, we do not know whether adding pre-operative radiation or ablation techniques, such as radiofrequency and cryotherapy, could reduce the seeding of viable tumor cells and are valuable treatment options despite their own complications and cost [16].…”
Section: Discussionmentioning
confidence: 99%
“…However Cruz et al describe first two case of tumor extravasation after VP [25]. Moreover study of Mohme et al indicated an increased dissemination of tumour cells into the vascular circulation after VP [26]. However available literature is lacking in discussion of risk of developing bone metastases after VP.…”
Section: Discussionmentioning
confidence: 99%
“…Bu veri, söz konusu girişim öncesi canlı tümör hücresi yayılımını azaltmaya yönelik stratejilerin (ameliyat öncesi RT, RFA, ameliyat esnasında RT gibi) önemini ortaya koymaktadır. [14] Perkütan sementoplasti, vertebrada popüler bir uygulama olmakla birlikte, pelvis (sıklıkla asetabulum) ve uzun kemiklerde de başarılı sonuçlar elde edilmektedir. [15] Uzun kemiklerde tek başına çimento uygulanması kırık gelişimine engel olmayacağı için, yöntemin metalik implant ile kombine edilmesi gereklidir.…”
Section: Kemi̇k çİmentosu (Pmma -Polimetil Metakrilat) Enjeksi̇yonlari unclassified